Efektivitas Media Video Interaktif terhadap Peningkatan Motivasi Belajar Siswa SD dalam Pembelajaran Sepak Bola - Firman Ramadhani Putra; Mochamad Ridwan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the effectiveness of interactive video media in enhancing elementary school students’ learning motivation in football lessons. The research was motivated by the low level of student engagement in physical education classes, which are often delivered in a monotonous and less interactive manner. This quantitative research employed a one-group pretest-posttest design. The sample consisted of 30 fifth-grade students from SDN Pakis I/368 Surabaya, selected through simple random sampling. Data were collected using a Likert-scale questionnaire to measure students' motivation before and after the intervention using interactive video media. The results showed an increase in the average score from 59.63 (pretest) to 75.33 (posttest). The normality test indicated that the data were normally distributed, and the paired sample t-test yielded a significance value of 0.000 (< 0.05), indicating a significant difference before and after the treatment. These findings suggest that interactive video media is effective in improving students’ learning motivation in football lessons. Therefore, this media can serve as an innovative instructional strategy to foster active student engagement in elementary physical education classes.